W=6

3w+6=4w, 3w-4w=-6, so, w=6

I would add 1 more step in between to make it clearer:

3w + 6 = 4w

As you mentioned, "It Is An Equation With Variables On Each Side!" which we do not like! So lets convert it to an equation with variable ONLY on one side - the type we are familiar

with :-)

Subtract 4w from both sides (of course if my weight = your weight then subtracting the same from both of us will land us up in new weights that are also equal!)

So,

3w + 6 - 3w = 4w - 3w

=> w = 6

3w + 6 = 4w

As you mentioned, "It Is An Equation With Variables On Each Side!" which we do not like! So lets convert it to an equation with variable ONLY on one side - the type we are familiar

with :-)

Subtract 4w from both sides (of course if my weight = your weight then subtracting the same from both of us will land us up in new weights that are also equal!)

So,

3w + 6 - 3w = 4w - 3w

=> w = 6